The Effectiveness of Propolis Antibacterial Against Staphylococcus aureus as an Alternative to Root Canal Irrigation - Ihsan Firdaus; Mirza Aryanto; Stanny Linda Paath; Nurani Hayati (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Irritation by bacteria can cause infection of the dental pulp, including Staphylococcus aureus which is the most resistant facultative microorganism that can cause root canal treatment failure. Root canal treatment is necessary to eliminate infection and protect the decontaminated tooth. Eliminating microorganisms from infected root canals is a complex task that requires various instrumentation techniques such as root canal irrigation, and the selection of irrigation materials that have antibacterial criteria, one of which is propolis. The antimicrobial properties of propolis are related to the presence of flavonoids. The antimicrobial activity of propolis is very effective against gram-positive and gram-negative bacteria. Purpose: To explain the inhibition of propolis extract as an alternative to irrigation solution in habituating the growth of Staphylococcus aureus bacteria in root canal treatment. Methods: This research is true experimental research conducted using the disc method in a laboratory. The samples tested were 24 samples in the form of Staphylococcus aureus bacteria in Tryptic Soy Agar (TSA) media. Variations of treatment concentration were propolis extract 2.5%, 5.25%, NaOCl 5.25% (positive control) and sterile distilled water (negative control). Results: The average inhibition of Staphylococcus aureus bacteria in propolis Trigona sp. 5.25% was 8.6 ± 0.5 mm. In positive control NaOCl 5.25% was 9.5 ± 0.9 mm. Hypothesis testing has a value of p=0,000 (p<0,05). Conclusion: There is an inhibitory activity against Staphylococcus aureus bacteria at a concentration of 5.25% propolis extract.